2019
DOI: 10.1002/1873-3468.13700
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from adenovirus (1970–2019)

Abstract: Animal viruses are well recognized for their ability to uncover fundamental cell and molecular processes, and adenovirus certainly provides a prime example. This review illustrates the lessons learned from studying adenovirus over the past five decades. We take a look back at the key studies of adenovirus structure and biophysical properties, which revealed the mechanisms of adenovirus association with antibody, cell receptor, and immune molecules that regulate infection. In addition, we discuss the critical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 257 publications
(283 reference statements)
0
32
0
Order By: Relevance
“…Adenoviruses are medium-sized (70–100 nm in diameter), non-enveloped icosahedral viruses composed of double-stranded linear DNA genome with an average length of 26–45 kb [ 1 ]. In humans more than 100 adenovirus types have been identified and classified into seven species (A to G) based on hemagglutination properties, oncogenicity in rodents, DNA homology, and genomic organization [ 2 , 3 ]. Human adenoviruses (HAdVs) cause significant numbers of respiratory, ocular, and gastrointestinal diseases and incidences of severe diseases caused by adenoviruses most occur in immunocompromised individuals or toddlers [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adenoviruses are medium-sized (70–100 nm in diameter), non-enveloped icosahedral viruses composed of double-stranded linear DNA genome with an average length of 26–45 kb [ 1 ]. In humans more than 100 adenovirus types have been identified and classified into seven species (A to G) based on hemagglutination properties, oncogenicity in rodents, DNA homology, and genomic organization [ 2 , 3 ]. Human adenoviruses (HAdVs) cause significant numbers of respiratory, ocular, and gastrointestinal diseases and incidences of severe diseases caused by adenoviruses most occur in immunocompromised individuals or toddlers [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how cells control virion stability is key to pathology and advances the field of synthetic virology, for example for the development of customized gene delivery vehicles and vaccines. Human AdVs and their interactions with cells are a highly advanced model of virus-host interactions at all levels, ranging from single cell infection, immunity, persistent and acute human disease to therapy and vaccination 35,56,68,69 . Human AdV particles are composed of major and minor capsid proteins conferring structural and accessory functions, such as DNA confinement, particle stability or membrane rupture 68,70,71 .…”
Section: Discussionmentioning
confidence: 99%
“…Human AdVs and their interactions with cells are a highly advanced model of virus-host interactions at all levels, ranging from single cell infection, immunity, persistent and acute human disease to therapy and vaccination 35,56,68,69 . Human AdV particles are composed of major and minor capsid proteins conferring structural and accessory functions, such as DNA confinement, particle stability or membrane rupture 68,70,71 . The latter is mediated by protein VI with an amphipathic helix interacting with sphingolipids 72,73,74,75,76,77,78,79 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their pathogenicity, HAdVs have gained a lot of attention as the experimental tools to study various molecular biology mechanisms and as the robust therapeutic tools suitable for disease treatment and prevention. Extensive cell biology and biochemistry studies using HAdV infections or HAdV-encoded proteins/RNAs have revealed the molecular mechanisms involved in anti-viral immune responses, virus uptake, mRNA processing, DNA replication and protein degradation [ 3 ]. This basic molecular virology knowledge has been instrumental to design genetically modified adenoviruses for therapeutic purposes.…”
Section: Human Adenovirusesmentioning
confidence: 99%
“…However, most of the functional studies have been carried out using the genetically almost identical virus types 2 and 5 (HAdV-2 and HAdV-5) [ 7 ]. HAdVs can infect a variety of cell types and they typically establish a lytic infection causing fast and efficient recipient cell lysis [ 3 ]. In addition to the relatively well-characterized lytic infection, some virus types, such as HAdV-2 and HAdV-5, can also establish enigmatic long-term persistent infections in B and T cells [ 8 , 9 ].…”
Section: Human Adenovirusesmentioning
confidence: 99%